2020
DOI: 10.1111/jvim.15690
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of preprandial and postprandial urine calcium to creatinine ratios in male Miniature Schnauzers with and without urolithiasis

Abstract: Background We aimed to identify a simple test for excessive calciuresis and predict calcium oxalate (CaOx) disease in Miniature Schnauzers. We investigated the impact of postprandial time on the urine calcium to creatinine ratio (UCa/Cr) in male dogs of this breed, with the goal of improving the utility of the UCa/Cr. Hypotheses (1) Significant differences will exist in preprandial and postprandial UCa/Cr between CaOx urolith‐forming and control Schnauzers. (2) The UCa/Cr will increase significantly from the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Only 1 of 62 dogs (1.6%) with UUT urolithiasis in this study had the urolith removed and analyzed for composition, whereas 58% of the LUT urolithiasis underwent compositional analysis. Similarly, a previous study found UUT uroliths in 8 of 24 Miniature Schnauzers undergoing abdominal radiography and ultrasonography; none were removed and analyzed [16]. It is important to note that 41% of the dogs in the present study had active or historic LUT urolithiasis, and nearly the same proportion had urolithiasis as the indication for abdominal radiographs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Only 1 of 62 dogs (1.6%) with UUT urolithiasis in this study had the urolith removed and analyzed for composition, whereas 58% of the LUT urolithiasis underwent compositional analysis. Similarly, a previous study found UUT uroliths in 8 of 24 Miniature Schnauzers undergoing abdominal radiography and ultrasonography; none were removed and analyzed [16]. It is important to note that 41% of the dogs in the present study had active or historic LUT urolithiasis, and nearly the same proportion had urolithiasis as the indication for abdominal radiographs.…”
Section: Discussionsupporting
confidence: 70%
“…This again parallels findings in the aforementioned study of Miniature Schnauzers undergoing abdominal radiography and ultrasonography. In that study, six out of eight of the dogs with UUT uroliths had active or historic LUT uroliths [16]. Cats likewise have a high co-occurrence of UUT and LUT uroliths, with one-third of cats with UUT uroliths having concurrent LUT uroliths [18].…”
Section: Discussionmentioning
confidence: 87%
“…7 Several risk factors coexist for CaOx urolith formation in dogs and include diet (including moisture content, treats, and trace elements), breed, genetics, age, sex, body condition score, voiding behavior, metabolic derangements, alterations in intestinal flora, and environmental factors. [12][13][14][15][16][17][18][19][20][21] Urine of dogs with CaOx uroliths often has higher relative supersaturation of these minerals 22 and the urine calcium-to-creatinine ratio is significantly higher in CaOx urolith-forming dogs compared to controls of the same breed, 14,23 suggesting calciuresis is an important factor. Diet is a key strategy used for prevention of CaOx urolithiasis, and a decrease in the proportion of CaOx-containing uroliths could indicate that diets marketed for CaOx prevention, diets with increased moisture content, or both could be effective in decreasing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Blood and urine samples were collected after 8 hours of withholding of food wherein the animals had free access to water to avoid the effect of calcium absorption during diet consumption. However, no postpandrial effect of UCa/Cr was observed within and between healthy and CaOx dogs 30 . Urinary calcium‐to‐creatinine ratio in CaOx dogs is significantly higher than that to healthy dogs during fasting and diet consumption 2,4 .…”
Section: Discussionmentioning
confidence: 92%